2013
DOI: 10.3329/bjdre.v3i2.16613
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of school oral health education program- A review

Abstract: The objectives of this review were to examine the various methods of school oral health instruction process and to identify success factors for oral health promotion along with the development of a future framework of action for Oral Health Promotion. In this review, the members of the working groups performed the systematic literature search, screening process, rating of the evidence, assessment of the evidence and presentation of the contents of the evidence to the reader. In this study we performed literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…(4,5) Pendidikan kesehatan gigi dan mulut adalah upaya untuk mempengaruhi seseorang agar berperilaku baik dan memotivasi untuk menjaga kesehatan gigi dan mulut, serta meningkatkan kesadaran masyarakat akan pentingnya kesehatan gigi dan mulut dan memberikan pengertian cara-cara memelihara kesehatan gigi dan mulut. (6) Anak-anak menghabiskan sebagian besar waktunya di sekolah, sehingga pengembangan lingkungan yang sehat dan adopsi perilaku mempromosikan kesehatan sesuai apabila dilakukan di sekolah. (7,8) Intervensi siswa sekolah dilakukan dengan tujuan agar pembelajaran tentang kebersihan dan kesehatan gigi bisa dilaksanakan sedini mungkin untuk meningkatkan pengetahuan siswa tentang pentingnya menjaga kesehatan, khususnya kesehatan gigi dan mulut serta kesehatan tubuh dan lingkungan pada umumnya.…”
Section: Latar Belakangunclassified
“…(4,5) Pendidikan kesehatan gigi dan mulut adalah upaya untuk mempengaruhi seseorang agar berperilaku baik dan memotivasi untuk menjaga kesehatan gigi dan mulut, serta meningkatkan kesadaran masyarakat akan pentingnya kesehatan gigi dan mulut dan memberikan pengertian cara-cara memelihara kesehatan gigi dan mulut. (6) Anak-anak menghabiskan sebagian besar waktunya di sekolah, sehingga pengembangan lingkungan yang sehat dan adopsi perilaku mempromosikan kesehatan sesuai apabila dilakukan di sekolah. (7,8) Intervensi siswa sekolah dilakukan dengan tujuan agar pembelajaran tentang kebersihan dan kesehatan gigi bisa dilaksanakan sedini mungkin untuk meningkatkan pengetahuan siswa tentang pentingnya menjaga kesehatan, khususnya kesehatan gigi dan mulut serta kesehatan tubuh dan lingkungan pada umumnya.…”
Section: Latar Belakangunclassified
“…13 Khan et al reported that the majority of school children had an adequate level of knowledge on oral health but had a low level of oral health practice. 4 Thus, research on oral health education should focus more on children's behavioral changes. Finally, although many oral health education interventions have been effective in improving oral health behaviors in developing and developed countries, 1,7,14 very few previous studies have focused on the effectiveness of age-specific and skill-based education on children's oral health-related behaviors in rural Bangladesh.…”
Section: Practice Pointsmentioning
confidence: 99%
“…[1][2][3] Previous studies have reported that poor oral health negatively affects the growth, development, and self-esteem of children, as well as their ability to eat, learn, and communicate. [1][2][3][4] Children with poor oral health are 12 times more likely to have restricted days away from school study, including missing school, comparing with those who have better oral health. 5 Globally each year, oral diseases, particularly dental caries, among children account for more than 50 million lost school hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey showed that 52% of the 147 participating pregnant women presented with the prevalence of moderate to severe dental erosion [19] . This erosion prevalence may be attributed not only to the increased consumption of low pH drinks (as predicted from market research data) but also from poor oral hygiene practice, lack of dental education, and unaffordable dental care among general population of Bangladesh [20][21][22] . Thus, identifying the sources of such erosion including the dental erosion potential of locally available soft drinks, energy drinks, fruit juices, and bottled drinking water has become significant.…”
Section: Introductionmentioning
confidence: 99%